2015
DOI: 10.3109/10428194.2015.1022769
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate-associated lymphoproliferative disorders: management by watchful waiting and observation of early lymphocyte recovery after methotrexate withdrawal

Abstract: No optimum treatment of iatrogenic immunodeficiency-associated lymphoproliferative disorders due to methotrexate in patients with rheumatoid arthritis (MTX-LPD) has yet been established, although MTX withdrawal is known to have a substantial effect on tumor regression. Here, we retrospectively analyzed 20 cases of MTX-LPD. Tumor shrinkage occurred in 18 of 20 cases, but only following MTX withdrawal. This tumor regression ratio was considerably better than in previous reports, and appeared due to longer "watch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
57
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 34 publications
9
57
1
1
Order By: Relevance
“…There is a growing interest in MTX-LPD regression without chemotherapy. The maximum shrinkage was obtained at approximately 8 weeks after the cessation of MTX (14). However, her FDG-PET/CT revealed extended involvement, which forced us administer R-CHOP because early chemotherapy has been reported to lead to a favorable outcome in IVLBCL (7,15).…”
Section: Discussionmentioning
confidence: 97%
“…There is a growing interest in MTX-LPD regression without chemotherapy. The maximum shrinkage was obtained at approximately 8 weeks after the cessation of MTX (14). However, her FDG-PET/CT revealed extended involvement, which forced us administer R-CHOP because early chemotherapy has been reported to lead to a favorable outcome in IVLBCL (7,15).…”
Section: Discussionmentioning
confidence: 97%
“…The histopathological features of MTX‐LPD are diverse, varying from polyclonal to monoclonal lymphocytosis . The frequency of extranodal involvement, including that of the lung, head, and neck, is relatively high; but hepatic involvement is extremely rare …”
Section: Discussionmentioning
confidence: 99%
“…Although there is no standard treatment for MTX‐LPD, approximately 60%‐90% of MTX‐LPD patients show spontaneous regression following MTX withdrawal, which is seen more frequently in cases positive for EBER on immunohistochemistry . Therefore, a watch‐and‐wait strategy may be the first choice for MTX‐LPD management, especially in EBER‐positive cases.…”
Section: Discussionmentioning
confidence: 99%
“…Saito et al and Inui et al reported that a significant decrease in absolute lymphocyte count at LPD diagnosis and its restoration after MTX withdrawal were associated with spontaneous regression of LPD that developed during MTX treatment 20,21) ; however, Takanashi et al reported opposing results 22) . Further research is therefore needed to determine if a rapid recovery of absolute lymphocyte count after MTX withdrawal represents a predictive factor for LPD regression.…”
Section: Discussionmentioning
confidence: 87%